Environmental Consortium Containing Pseudomonas and Bacillus Species Synergistically Degrades Polyethylene Terephthalate Plastic - Roberts, Cameron; Edwards, Sabrina; Vague, Morgan; León-Zayas, Rosa; Scheffer, Henry; Chan, Gayle; Swartz, Natasja A.; Mellies, Jay L. (mSphere, 2020)
While several research groups are utilizing purified enzymes to break down postconsumer PET to the monomers TPA and ethylene glycol to produce new PET products, here, we present a group of five soil bacteria in culture that are able to partially degrade this polymer. To date, mixed Pseudomonas spp. and Bacillus spp. biodegradation of PET has not been described, and this work highlights the possibility of using bacterial consortia to biodegrade or potentially to biorecycle PET plastic waste. Plastics, such as polyethylene terephthalate (PET) from water bottles, are polluting our oceans, cities, and soils. While a number of Pseudomonas species have been described that degrade aliphatic polyesters, such as polyethylene (PE) and polyurethane (PUR), few from this genus that degrade the semiaromatic polymer PET have been reported. In this study, plastic-degrading bacteria were isolated from petroleum-polluted soils and screened for lipase activity that has been associated with PET degradation. Strains and consortia of bacteria were grown in a liquid carbon-free basal medium (LCFBM) with PET as the sole carbon source. We monitored several key physical and chemical properties, including bacterial growth and modification of the plastic surface, using scanning electron microscopy (SEM) and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) spectroscopy. We detected by-products of hydrolysis of PET using 1 H-nuclear magnetic resonance ( 1 H NMR) analysis, consistent with the ATR-FTIR data. The full consortium of five strains containing Pseudomonas and Bacillus species grew synergistically in the presence of PET and the cleavage product bis(2-hydroxyethyl) terephthalic acid (BHET) as sole sources of carbon. Secreted enzymes extracted from the full consortium were capable of fully converting BHET to the metabolically usable monomers terephthalic acid (TPA) and ethylene glycol. Draft genomes provided evidence for mixed enzymatic capabilities between the strains for metabolic degradation of TPA and ethylene glycol, the building blocks of PET polymers, indicating cooperation and ability to cross-feed in a limited nutrient environment with PET as the sole carbon source. The use of bacterial consortia for the biodegradation of PET may provide a partial solution to widespread planetary plastic accumulation. IMPORTANCE While several research groups are utilizing purified enzymes to break down postconsumer PET to the monomers TPA and ethylene glycol to produce new PET products, here, we present a group of five soil bacteria in culture that are able to partially degrade this polymer. To date, mixed Pseudomonas spp. and Bacillus spp. biodegradation of PET has not been described, and this work highlights the possibility of using bacterial consortia to biodegrade or potentially to biorecycle PET plastic waste.